DEATH OF PEAFOWL CHICK (PAVO CRISTATUS) DUE TO FOREIGN BODY IN THE GIZZARD: A CASE REPORT - Xiaoxia Du; Ahrar Khan; Weiwei Zhou; Yingying Gao; Bayi Jiang (Journal of Animal and Plant Sciences, 2022)
Pheasants occupy the most auspicious place among the birds kept by many people at home. Among pheasants, one of the most beautiful birds is the common peafowl. The peafowls are omnivorous in nature. They can eat seeds, plants, fruits, insects, ants, flies, snakes, and amphibians. They prefer to live in farmlands, bushlands, forests, and other regions with access to low height trees, and prefer to live near the human tenancies. They may eat such inanimate materials along with food, especially eating inanimate materials increased when kept in houses. A peafowl chick died after about 10 days of illness in this case study. Post-mortem revealed congested buccal mucosa. The tongue was dragged down by a thread wrapped around its base. The thread through the esophagus went into the proventriculus and entered the gizzard. The proventriculus was hemorrhagic; however, the gizzard did not show any lesion. The proventriculus measured 4.5 cm length x 1.5 cm width while the gizzard was 3.5 cm length x 2.5 cm width. The inanimate materials present in the gizzard were having length 3.5 cm and width 1.5 cm. The thread was of nylon and tied up inanimate material was made of nylon/cotton threads and human hairs. Nylon thread was so lengthy that it went into the gizzard in double layer and led to the death of the peafowl chick. This chick could have been saved if presented for treatment 2-3 days earlier by pulling out inanimate materials via proventriculus and esophagus. When peafowls are in the backyards or in the houses, people need to ensure that nothing (inanimate material) is available for them to swallow while they are set free for sometimes.
Keywords: Mitochondrial D-loop; Phylogenetic study; Saudi goat breeds